Kurikulum Merdeka dalam Pandangan Filsafat Esensialisme - Nurur Rubingah; Pipit Saraswati Indriasari; Endang Fauziati; Indri Indri (Pusat Riset dan Inovasi Nasional, 2023)
Essentialism is a philosophical stream that emphasizes culture and efforts to prepare humans for life. The independent curriculum aims to improve the education system in Indonesia during the pandemic and post-pandemic as well as to form a Profil Pelajar Pancasila. The research method used in this research is descriptive qualitative using library research. The implication of this research is the conformity of the views in this essentialist philosophy to the independent curriculum.